Exposure to whole-body vibration and hospitalization due to lumbar disc herniation - Wahlström, Jens (Int Arch Occup Environ Health, 2018)
OBJECTIVE: The aim was to examine if exposure to whole-body vibration (WBV) increases the risk for hospitalization due to lumbar disc herniation. METHODS: The study basis is a cohort of 288,926 Swedish construction workers who participated in a national occupational health surveillance programme from 1971 until 1992. Job title, smoking habits, body weight, height and age were registered at the examinations. Assessment of WBV were made for each of the constituent occupations by constructing a job-exposure matrix (JEM). Exposure to WBV was graded on a scale from 0 to 5. In addition, the occurrence of hospitalization due to lumbar disc herniation from January 1st 1987 until December 31st 2010 was collected from a linkage with the Swedish Hospital Discharge Register. Poisson regressions were used to estimate relative risk with 95 percent confidence intervals (95% CI), adjusting for age, height, weight and smoking, using white-collar workers and foremen as a reference group. RESULTS: There was an increased risk for hospitalization due to lumbar disc herniation for workers in the construction industry exposed to medium to high WBV compared to white-collar workers and foremen 1.35 (1.12–1.63). When restricting the analyses to include workers 30–49 years of age at the time of the hospital admission the risk was 1.69 (95% CI 1.29–2.21). CONCLUSION: This study further supports that occupational exposure to whole-body vibration increases the risk for hospitalization due to lumbar disc herniation. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00420-018-1316-5) contains supplementary material, which is available to authorized users.